2015
DOI: 10.3171/2014.10.spine14501
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in primary spinal osteochondroma: a multicenter study of 27 patients

Abstract: OBJECT Clinical outcomes in patients with primary spinal osteochondromas are limited to small series and sporadic case reports. The authors present data on the first long-term investigation of spinal osteochondroma cases. METHODS An international, multicenter ambispective study on primary spinal osteochondroma was performed. Patients were included if they were diagnosed with an osteochondroma of the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 30 publications
1
27
0
7
Order By: Relevance
“…In primary spinal tumors, Enneking and Weinstein-Boriani-Biagini (WBB) classifications demonstrated moderate interobserver reliability and substantial to near-perfect intraobserver reliability with respect to staging and treatment decision making, but less than moderate interobserver reliability in interpreting the Enneking local tumor extension and WBB sector. 21 While existing evidence has reported that these classification systems improve disease control and survival in patients with primary spinal bony tumors 22-25 , they are not easily applicable to spinal schwannomas. However, Sridhar et al 26 have proposed a useful classification of spinal schwannomas based on radiological imaging (Table 4 and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In primary spinal tumors, Enneking and Weinstein-Boriani-Biagini (WBB) classifications demonstrated moderate interobserver reliability and substantial to near-perfect intraobserver reliability with respect to staging and treatment decision making, but less than moderate interobserver reliability in interpreting the Enneking local tumor extension and WBB sector. 21 While existing evidence has reported that these classification systems improve disease control and survival in patients with primary spinal bony tumors 22-25 , they are not easily applicable to spinal schwannomas. However, Sridhar et al 26 have proposed a useful classification of spinal schwannomas based on radiological imaging (Table 4 and Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The most are located in the posterior part of the vertebrae, but in 27% of patients MRI can reveal the extension into the spinal canal. Although rare, a symptomatic compression of the medulla can occur with serious neurologic consequences (36). Therefore, spinal osteochondromas require careful management, thorough follow-up and a MRI screening for patients in the growing years in order to prevent serious disability (37).…”
Section: Neurovascular Disordermentioning
confidence: 99%
“…1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, 48,52,65,74,86,93,98 and prior studies have identified anatomical location, tumor size, tumor histology, extent of resection, surgical approaches, age, functional status, comorbidities, preoperative medication (steroid use, morphine), longer operative time, insurance status, early postoperative complications, and adjuvant chemotherapy and radiotherapy as factors associated with postoperative morbidity and mortality. 1,[18][19][20][21][22][23][24]39,41,42,44,48,51,52,56,58,66,69,78,92,99 Nevertheless, many of these previous publications were retrospective, institutional studies, 10,11,55,60,65,87,…”
mentioning
confidence: 99%
“…1,13,14,16,17,26,27,30,31,38,63,93,[95][96][97][98] However, surgical approaches to spinal tumors often necessitate extensive reconstruction of the spinal column and may require adjuvant chemotherapy or radiation; therefore, perioperative complication rates after spinal tumor surgery are higher than in other spinal operations. [34][35][36][46][47][48]50,52,65,67,68,78,80,81,[86][87][88]95,100 It is especially important to understand the incidence and predictive factors for adverse events in spinal oncology patients, as a single complication may be associated with morbidity, mortality, and costs. 1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, …”
mentioning
confidence: 99%